Early monitoring of plasma KRAS G12C with digital PCR predicts antitumor response to immunotherapy or sotorasib in advanced NSCLC: A brief report - Andrea De Giglio; Federico Zacchini; Giulia Venturi; Alessandro Di Federico; Claudia Parisi; Filippo Gustavo Dall’Olio; Ilaria Ricciotti; Valentina Favorito; Ambrogio Gagliano; Dario De Biase; Thais Maloberti; Annalisa Altimari; et al. (The Journal of Liquid Biopsy)
Background: The frontline management of non-oncogene addicted non-small cell lung cancer (NSCLC) involves immune-checkpoint inhibitors (ICI) alone or combined with chemotherapy (CT-ICI). The dynamic landscape of KRAS-positive NSCLC presents a spectrum of treatment options, including ICIs, targeted therapy and combination strategies currently under investigation. Methods: We conducted a prospective project to detect circulating tumor DNA (ctDNA) in patients with KRAS G12C, advanced NSCLC. We included patients undergoing upfront ICIs or subsequent line sotorasib. We planned three-time points: baseline (T0), after 3 months of treatment (T1) and at disease progression (T2). Results: 24 consecutive patients have been included. The most frequent baseline characteristics were: nonsquamous histology (95.8%), male gender (62.5%), ECOG PS 0–1 (79.2%), <3 metastatic sites (13/24, 54.2%). 18 patients (75%) received ICI-based strategies and 6 patients (25%) sotorasib. Patients with liver metastases (p ​= ​0.01) and those with >3 metastatic sites (p ​= ​0.002) exhibited significantly elevated ctDNA. Median overall survival (OS) was 7.5 months, progression-free survival (PFS) was 4.0 months and the objective response rate (ORR) was 33.3%. Higher AF correlated with an increased risk of death (HR 1.04, p ​= ​0.03), though not progression. The mOS was 7.5 months (95% CI, 1.91-NR) in high-AF group and 11.3 months (95% CI, 6.6-NR) in low-AF group (p ​= ​0.38). Notably, a reduction in plasma DNA levels was significantly associated with objective response (p ​= ​0.01). Two patients received a T2 dosage showing increased ctDNA levels after a previous reduction associated with response. Conclusion: Early monitoring with ctDNA may offer potential benefits in the evolving scenario of KRAS G12C NSCLC treatment.